Anal dilation during labor - Kalis, Vladimir; Karbanova, Jaroslava; Bukacova, Zuzana; Bednarova, Barbora; Rokyta, Zdenek; Kralickova, Milena (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2010)
OBJECTIVE: To determine the incidence and range of anal dilation during the final phase of the second stage of labor and shortly after delivery; determine whether parity affects anal dilation; and obtain anthropometric data for future projects. METHODS: The anal diameter was measured on admission, when the fetal head crowned, and after suturing perineal injury in 142 women delivered between August 2008 and May 2009 at University Hospital Pilsen and District Hospital Klatovy, in the Czech Republic. RESULTS: The anus was dilated during the second stage of labor in all women, and differences between primiparas and multiparas were not significant. The medians for both the anteroposterior and transverse diameters were 25 mm. No measured variable was statistically associated with anal sphincter dilation. CONCLUSION: Anal dilation during the second stage of labor causes anthropometric changes to the perineum. This ought to be considered when designing anthropometric studies and in studies aiming at minimizing anal sphincter trauma during delivery.
Keywords: Pregnancy; Delivery, Obstetric; anální kanál; porodnické kleště; Perineum; Cohort Studies; dilatace patologická; Humans; druhá doba porodní; Anal Canal; komplikace porodu; Female; kohortové studie; vedení porodu; Labor Stage, Second; ženské pohlaví; incidence; Incidence; Obstetric Labor Complications; Dilatation, Pathologic; mladý dospělý; Adult; Young Adult; Obstetrical Forceps; dospělí; lidé; těhotenství; perineum